The development of autoantibody diagnostics in renal cell carcinoma - Tsoumpeli, Maria (2021)
Renal Cell Carcinoma (RCC) is one of the most commonly diagnosed cancers worldwide and it lacks an early diagnostic biomarker. Here, the autoantibody responses against tumour-associated antigens were mapped to identify mimotopes that could be used in serological assays. An epitope mapping technique was applied that coupled the diagnostic potential of phage display peptide libraries, with the analytical depth of Next Generation Sequencing, a process called Next Generation Phage Display (NGPD). Firstly, a synthetic 16mer peptide phage library was constructed (diversity 5 x 109). This was used in the optimisation of an epitope mapping approach using known mAbs in solution/sera. The method consistently identified panels of mAb specific peptides, confirmed by phage-peptide ELISA. In addition, the NGS frequencies of the enriched peptides could be summed (an immunosignature) and used to distinguish between spiked and non-spiked sera samples. This immunosignature method was at least as sensitive and specific as ELISAs using phage-peptide mimotopes. The optimised NGPD approach was applied to sera collected from a mouse model for early stage RCC (TRACK model). In total, 14 (training set) and 29 (testing set) samples from TRACK or Wild Type (WT) mice were assessed. Enriched peptides identified by NGS (n=42) were screened against TRACK and WT sera by ELISA, and particularly one of them showed 72% sensitivity and 85.7% specificity, when sera from 12 month or older mice were used. The immunosignature approach was also applied and was 76.5% sensitive and 100% specific, when applied to sera from 12 month or older TRACK mice. The strategy was then applied to sera derived from cc-RCC (n=100) or healthy (n=50) patients using same phage-peptide sub-library enriched against RCC–specific autoantibodies in TRACK mice. An immunosignature assay demonstrated 85% sensitivity and 90% specificity in the training cohort used to develop the assay, and 30% sensitivity and 100% specificity in a test cohort. Taken all the data together, mapping host’s autoimmune response against RCC by NGPD could be a novel and effective strategy to developing serological based diagnostics to cc-RCC and other diseases that may trigger an autoantibody response.